Markov processes, semigroups, and generators - Kolokolʹt͡sov, V. N. (Vasiliĭ Nikitich) (De Gruyter studies in mathematics ;, 2011)
This work offers a highly useful, well developed reference on Markov processes, the universal model for random processes and evolutions. The wide range of applications, in exact sciences as well as in other areas like social studies, require a volume that offers a refresher on fundamentals before conveying the Markov processes and examples for applications. This work does just that, and with the necessary mathematical rigor.